2014
DOI: 10.1155/2014/380850
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cytotoxicity and Genotoxicity ofAcacia aromaLeaf Extracts

Abstract: Acacia aroma, native plant from San Luis, Argentina, is commonly used as antiseptic and for healing of wounds. The present study was conducted to investigate the in vitro cytotoxicity and genotoxicity of hot aqueous extract (HAE) and ethanolic extract (EE) of A. aroma. The cytotoxic activity was assayed by neutral red uptake assay on Vero cell. Cell treatment with a range from 100 to 5000 μg/mL of HAE and EE showed that 500 μg/mL and 100 μg/mL were the maximum noncytotoxic concentrations, respectively. The CC5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Reviewing the scientific literature showed that this study is the first of its kind that studied the genotoxicity of C. spinosa extract on prokaryotes using molecular fingerprinting based on ERIC-PCR and RAPD-PCR techniques. Besides, many plants were previously examined to investigate their genotoxic potential using different techniques [21,22,28,[34][35][36][37][38][39]. In this study, RAPD-PCR and ERIC-PCR profiles showed many significant differences between the treated and untreated E. coli strain.…”
Section: Discussionmentioning
confidence: 95%
“…Reviewing the scientific literature showed that this study is the first of its kind that studied the genotoxicity of C. spinosa extract on prokaryotes using molecular fingerprinting based on ERIC-PCR and RAPD-PCR techniques. Besides, many plants were previously examined to investigate their genotoxic potential using different techniques [21,22,28,[34][35][36][37][38][39]. In this study, RAPD-PCR and ERIC-PCR profiles showed many significant differences between the treated and untreated E. coli strain.…”
Section: Discussionmentioning
confidence: 95%
“…Using computerized image analysis system, the data were analyzed. By the ratio of tail to head length the extent of DNA damages was scored as follows: <5% -no damage, 5-20% low damage, 21-40% medium damage, 41-95% high damage, and >95% complete damage [15][16][17][18].…”
Section: Scge (Comet Assay)mentioning
confidence: 99%
“…A study by Nath et al (2017) revealed that Acorus calamus, used in folk medicine in India, caused genotoxic and hepatotoxic effects in its users. Several medicinal plants from Ethiopia, Argentina, Serbia, and parts of Africa have also been shown to produce genotoxic effects (Mattana et al 2014;Seukep et al 2014; Kahaliw et al 2018;Madić et al 2019). Inspite of their e cacy, medicinal plants can also be a source of toxic elements (Yuan et al 2011).…”
Section: Introductionmentioning
confidence: 99%